Martin Luther en teologiebeoefening in die toekoms - Wyk, I. W. C.van (HTS teologiese studies, 2015)
Martin Luther and doing theology in the future. The Netherdutch Reformed Church of Africa prides itself for the fact that she has always appreciated the German-Lutheran tradition. The Reformed Theological College has for 15 years contributed to the appreciation of this tradition. This article wants to encourage the new leadership to keep this legacy alive. The main aspects of Luther’s theology are explained. These aspects are: prayer (oratio), meditation (meditatio), constitation (tentatio), grace of the Spirit (gratia Spiritus), exegesis (sedulalectio), and the use of other sciences in understanding the Bible (bonarum atrium cognitia). Attention is also given to the subject-matter of Theology as well as the notion of humbleness.